Prevention, promotion and restoration of worker´s oral health - Érica Silva Carvalho; Sandra Regina Hortense; Lívia Maria Vieira Rodrigues; José Roberto de Magalhães Bastos; Arsenio Sales Peres (Faculdade São Leopoldo Mandic, 2009)
In the course of history the terms related to workers, their health and work environment have been changed: from Medical Labor Health to Occupational Health through to the Worker's Health. This aim of this article is to demonstrate the importance of the worker's oral health, by means of the studies of several authors. This literature review draws attention to the importance of knowing the dental problems that may affect workers, with the intention of analyzing the epidemiology, etiology and pathology in addition to understanding the impact they would cause on the quality of life, oral health promotion and prevention. This goal stems from the dentist's importance to the Worker's Health, preventing dental absenteeism, as orofacial pain may alter the conditions of life and work of the individual to a greater extent than other systemic conditions such as diabetes and high blood pressure do. Occupational Dentistry has collaborated with worker's health both in the public and private spheres, because what really is really being sought is a worker with adequate oral health conditions for his/her work activities and an improvement in the worker's quality of life.